Pengaruh Tarif, Keadilan, Sistem Perpajakan, Teknologi dan Informasi, dan Sanksi Perpajakan terhadap Persepsi Wajib Pajak Mengenai Etika Penggelapan Pajak pada KPP Pratama Tegal - Andina Putri Adisty; Yuniarti Herwinarni; Didi Ardiansah (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2017)
This research aims to determine whether there is the influence of tax rates, justice, taxation system, technology and taxation information, and sanctions taxation both simultaneously and partially to the taxpayer's perception of tax evasion ethics.This type of research is correlational. The population used is individual taxpayers and taxpayers registered in the KPP Pratama Kota Tegal. As well as the samples used are individual taxpayers registered in KPP Pratama Kota Tegal 2018 method of sampling by incidental sampling. Source of data used is primary source obtained from spreading of questioner to responder. Data analysis method using classical assumption test, multiple regression analysis, simultaneous test (F test), hypothesis test (t test), and coefficient of determination. The results showed that the tax rate, justice, taxation system, taxation technology and information, and tax sanction have a significant effect simultaneously to the taxpayer's perception about tax evasion ethics, tax rate significantly partially influence the taxpayer's perception about tax evasion ethics, partially significant effect on the taxpayer's perception of tax evasion etiquette, taxation system has a significant effect partially on the taxpayer's perception of tax evasion ethics, technology and information has no significant effect partially on the taxpayer's perception of tax evasion ethics, and tax sanctions have significant effect partially to the taxpayer's perception of tax evasion ethics.